The Efficacy and Safety of Elobixibat for the Elderly with Chronic Constipation: A Multicenter Retrospective Cohort Study. (28th April 2020) - Tomie, Akira; Yoshida, Naohisa; Kugai, Munehiro; Hirose, Ryohei; Dohi, Osamu; Inoue, Ken; Okuda, Kotaro; Motoyoshi, Takayuki; Fukumoto, Kohei; Inagaki, Yoshikazu; Yoriki, Hiroyuki; Inada, Yutaka; et al.
Abstract : Backgrounds and Aims . Elobixibat is a bile acid transporter inhibitor indicated for constipation. Previous studies were performed mainly for the nonelderly and were biased to female. We analyzed the efficacy of elobixibat also for the elderly and male. Materials and Methods . This was a multicenter retrospective cohort study. The subjects were patients aged ≥20 years treated for chronic constipation from May 2018 to November 2019 at 12 related institutions. Patients were divided into ≤74 years and ≥75 years old. Elobixibat at 10 mg/day was prescribed for two weeks. We then analyzed the discontinuation due to ineffectiveness, change of spontaneous bowel movements (SBM), stool consistency, the time until the first SBM, adverse events, and effect-related factors. Results . There were 140 cases (61 males) evaluated, with an average age of 72.1 ± 13.6 years (≤74 years: 71 cases; ≥75 years: 69 cases). The discontinuation rate was 7.9%. The SBM (times/week) increased from 2.86 to 6.08 (p < 0.001 ). The overall SBM improvement rate was 74.0% (≤74 years: 78.2% vs. ≥75 years: 68.9%, p = 0.31 ; male: 75.0% vs. female: 73.3%, p = 0.78 ). The overall improvement rate of stool consistency was 59.6% (≤74 years: 62.9%, ≥75 years: 56.1%, p = 0.42 ). The time until the first SBM (hours) for those ≤74 years and ≥75 years was 17.2 ± 14.3 and 11.2 ± 8.4 (p = 0.04 ). Adverse event rates for those ≤74 years and ≥75 years were 28.2% and 10.1% (p < 0.01 ). There were no significant effect-related factors for gender, age, and use of laxatives. Conclusions . Short-period elobixibat is shown to be effective also for the elderly and male.